SERPIH PEMIKIRAN JEAN JACQUES ROUSSEAU TERHADAP PENDIDIKAN - Rahmadi Rahmadi; Rusma Yulidawati (Tarbawi, 2021)
This research aims to investigate Jean Jacques Rousseau's thoughts on education and its implications in modern educational practices. Rousseau advocated for an education that emphasizes freedom, authenticity, and the natural happiness of human beings. The research method used is the analysis of Rousseau's primary texts, such as "Emile" and "The Social Contract", as well as related literature studies. This research method uses a literature review. The results show that Rousseau emphasizes the importance of education that accommodates the natural human nature and returns humans to their original natural state. The implications of Rousseau's thoughts on modern education highlight the importance of an educational approach that frees humans from evil and returns them to their original nature or natural human beings. This research contributes to understanding the concept of natural education from Rousseau's perspective and explains its relevance in the context of contemporary education.